Evaluation of Errors in Seismic Analysis Methods by Considering Lateral Stiffness Irregularities in Construction Projects - Rahmati, Jamal (ExcelingTech, 2020)
Abstract. Basically, among the various stages that are considered when designing a building for earthquake resistance, the decision stage about building configuration is of fundamental importance. One of the important factors that has a significant impact on the seismic performance of the building is its regularity or irregularity in plan and height. Most of those with irregular configurations are more damaged by earthquakes. Therefore, it is important to set criteria for detecting irregularities in structures. In this study, in order to investigate the error rate of seismic analysis methods (static equivalent, spectral and time history) in intermediate structures with irregularity of hardness, 4 5-story steel samples with dual flexural frame system and bracing with different states of irregularity in height in soft SAP software has been modeled. The results showed that the equivalent static analysis method always provides conservative and somewhat uneconomical values compared to other methods, so it can be said that for static buildings, equivalent static analysis is reliable. Any analysis of time history better than spectral analysis better represents the behavior of the structure during an earthquake.